Optimization of cyanidation tailings bioremediation adding nutrients and microorganisms - Hurtado, Jasmin (2012)
The objective of this project was to find optimum parameters for the development of bioremediation process of cyanidation tailings by addition of nutrients and microorganisms. It was tested the use of sulfate-reducing bacteria (SRB) to stabilize metal ions through the formation of sulphides and; bacteria able to biodegrade cyanide (BC). Factorial experiments were conducted at level of columns. SRB from Cyanidation tailings were isolated and BC proceeded from pregnant solution of cyanidation. BSR and BC were adapted to tailings. A column test was performed to try: 1. the effect of using 1 and 10 mM lactate to increase the activity of BSR and 2. Addition of 0,1 and 1 mM sodium acetate and phosphoric acid to improve the activity of BC. In order to optimize parameters, it was tested in columns, effect of a mixed culture (SRB-BC) and nutrients (1 mM lactate and Acetate 1mM). Nutrients were found to increase the reduction of sulfate to 48% (average) and the addition of inoculums to 42%. Bioremediation of cyanide was 12%. It was not shown effect on the addition of nutrients or inoculums on Cyanide degradation. Two additional tailings were tested and the addition of 1 mM sodium lactate allowed the induction of BSR in 8 days in one of them.